2016
DOI: 10.1080/10286020.2015.1124866
|View full text |Cite
|
Sign up to set email alerts
|

Two new tetracyclic triterpenoids from the barks of Melia azedarach

Abstract: Two new tetracyclic triterpenoids, together with 21 known compounds, were isolated from the barks of Melia azedarach. The structures of new compounds were elucidated by the means of HRESIMS, 1D NMR, 2D NMR, and X-ray crystallography analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It has been known that about 25%–48% of current approved therapies for cancer patients by the FDA (Food and Drug Administration) are derived from plants [5, 6]. According to statistics, hundreds of anticancer agents are either pure natural products, natural product derivatives or synthetic compounds with pharmacophores mimicking natural products [7]. Thus, natural products could be considered as a potential source of new anticancer drugs to combat NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that about 25%–48% of current approved therapies for cancer patients by the FDA (Food and Drug Administration) are derived from plants [5, 6]. According to statistics, hundreds of anticancer agents are either pure natural products, natural product derivatives or synthetic compounds with pharmacophores mimicking natural products [7]. Thus, natural products could be considered as a potential source of new anticancer drugs to combat NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…These toxic components affect as enterotoxins and neurotoxins (Oelrichs et al, 1983). Alkaloids, flavonoids, limonoids, steroids and triterpenoids are also isolated from leaves and barks of tree (Ge et al, 2016;Pan et al, 2014). Other potentially toxic components comprise azadarin (alkaloid), meliotannic acid, benzoic acid, and resins such as azaridine, parisine, and margosinine (Plumlee, 2003).…”
Section: Toxic Componentsmentioning
confidence: 99%
“…Natural products and their derivatives have been used as anticancer agents and present a potential source of new drugs to combat cancer 22 24 . To identify potential YAP/TAZ inhibitors, we previously performed a YAP/TAZ luciferase reporter activity-based screening of a library of natural products (Selleckchem, Houston, TX, USA), and found that apigenin decreased YAP/TAZ activity.…”
Section: Introductionmentioning
confidence: 99%